Mercy Thompson. Hopcross Jilly - Briggs, Patricia; Hoskin, Rik (Briggs, Patricia. Mercy Thompson novels., 2015)
Mercy is a shapeshifting coyote and honorary member of the Tri-Cities werewolf pack. When the pack stumbles upon the buried bones of numerous dead children, she shapeshifts into a mystery of the legendary fae--a mystery that draws Mercy's stepdaughter Jesse into the fray! The supernatural romance series Mercy Thompson continues in this all-new, original story by New York Times bestselling author, Patricia Briggs, exclusively created for the comic book medium! Collects the six-issue Mercy Thompson comic book series from 2014-2015, a story set in official continuity.